2019
DOI: 10.1093/nar/gkz800
|View full text |Cite
|
Sign up to set email alerts
|

A single ChIP-seq dataset is sufficient for comprehensive analysis of motifs co-occurrence with MCOT package

Abstract: Recognition of composite elements consisting of two transcription factor binding sites gets behind the studies of tissue-, stage- and condition-specific transcription. Genome-wide data on transcription factor binding generated with ChIP-seq method facilitate an identification of composite elements, but the existing bioinformatics tools either require ChIP-seq datasets for both partner transcription factors, or omit composite elements with motifs overlapping. Here we present an universal Motifs Co-Occurrence To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(70 citation statements)
references
References 57 publications
2
56
0
Order By: Relevance
“…Indeed, Gbox motifs were found to be enriched in close proximity to auxin response elements (AuxREs) (Weiste and Dröge-Laser, 2014;Ulmasov et al, 1995) and they are overrepresented in auxin-responsive and ARF-binding regions (Berendzen et al, 2012;Cherenkov et al, 2018). To test the co-occurrence of ARFs and G-class bZIPs motifs, we applied the Motifs Co-Occurrence Tool (MCOT) (Levitsky et al, 2019) to ARF5 and ARF2 peaks taken from genome-wide DAP-seq profiles (O'Malley et al, 2016). We analyzed all possible combinations of AuxREs (ARF2/5 motifs) and Gboxes (GBF3 and bZIP16/68 motifs) with any overlap or spacer lengths below 30 nucleotides, and found that bZIP68 and ARF5 motifs overlap (P-value<5E-40) ( Fig.…”
Section: Gbf1 and Gbf2 Can Interact With Mpmentioning
confidence: 99%
“…Indeed, Gbox motifs were found to be enriched in close proximity to auxin response elements (AuxREs) (Weiste and Dröge-Laser, 2014;Ulmasov et al, 1995) and they are overrepresented in auxin-responsive and ARF-binding regions (Berendzen et al, 2012;Cherenkov et al, 2018). To test the co-occurrence of ARFs and G-class bZIPs motifs, we applied the Motifs Co-Occurrence Tool (MCOT) (Levitsky et al, 2019) to ARF5 and ARF2 peaks taken from genome-wide DAP-seq profiles (O'Malley et al, 2016). We analyzed all possible combinations of AuxREs (ARF2/5 motifs) and Gboxes (GBF3 and bZIP16/68 motifs) with any overlap or spacer lengths below 30 nucleotides, and found that bZIP68 and ARF5 motifs overlap (P-value<5E-40) ( Fig.…”
Section: Gbf1 and Gbf2 Can Interact With Mpmentioning
confidence: 99%
“…There are a few main differences between PscanChIP and other methods for the same task. The presence/absence of a motif instance in a region is evaluated with a score, ranging from 0 to 1, instead of a yes/no decision (binding motif present/absent) as for example in recent works (Dergilev et al, 2017;Czipa et al, 2020;Levitsky et al, 2019), which are also focused on the analysis of regions surrounding ChIP-Seq summits. Mean and variance of scores of best motif instances in each of the summit regions are in turn employed by PscanChIP to assess motif enrichment not only with respect to regions flanking peaks (local enrichment), as in similar tools (Zhang et al, 2011;Bailey and MacHanick, 2012), but also with respect to the rest of the genome, providing a more accurate evaluation of their significance.…”
Section: Defining Binding and Recruitment Rules Through Motif Analysismentioning
confidence: 99%
“…An orthogonal approach is to analyze regions resulting from a single ChIP-Seq experiment for enrichment of sequence motifs known to represent sites be bound by other TFs, as for example in (Wang et al, 2012;Levitsky et al, 2019). Candidate TFs thus identified can be likely members of the same regulatory module.…”
Section: Introductionmentioning
confidence: 99%
“…This approach should exclude them from clinical studies, which consequently could become more targeted and less expensive. Although the accuracy of current genome-wide computational predictions remains below the applicability threshold for clinical SNP tests [26], this accuracy increases every year [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%